Analisis Komperatif Kinerja Keuangan Bank Syariah dan Bank Konvensional Antara BRI dan BNI dengan Pendekatan Camel - Akhmadi Akhmadi (Universitas Batanghari Jambi, 2021)
Bank is an important financial institution so that its performance needs to be maintained in order to work properly and optimally. The purpose of this study is to analyze the comparison of the financial performance of Islamic banks and conventional banks in Indonesia. This research is a comparative quantitative research using a comparison design of two averages from two independent populations. The samples in this study were 2 Islamic banks (Bank Negara Indonesia Syariah and Bank Rakyat Indonesia Syariah) and 2 conventional banks (Bank Negara Indonesia and Bank Rakyat Indonesia). The bank's financial performance assessment method used in this study is CAMEL with financial ratios namely CAR, NPL, NIM, ROA, BOPO, and LDR. Data were analyzed using the mean difference test of two unpaired groups (independent sample t-test). The results of this study indicate that there are significant differences in the ratio of NPL, ROA, BOPO, LDR between Islamic banks and conventional banks. The results of the analysis show that the financial performance of Islamic banks is better based on the ratio of NPL, NIM, BOPO, LDR. While the financial performance of conventional banks is better based on the ratio of CAR, ROA.